Total water potential variation in a soil table land topsequence, during two years - Souza, Luciano da Silva; Paiva, Arlicélio de Queiroz (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to evaluate, fortnightly, during 1996/1997, the total soil water potential variation in a tableland topsequence in Sapeaçu county, BA, Brazil. This topsequence had the following characteristics: a) length of 190 m; b) slope of 0.097 m m-1; c) orange as growing crop; d) the upper third with a cohesive argisolic Yellow Latosol; e) the middle third with a cohesive Yellow Argisol; and f) the lower third with a non-cohesive Gray Argisol. Soil water was estimated by neutron probe at depths of 0.30, 0.70, 1.10, and 1.50 m. Based on water retention curves, matric potential and, in sequence, total soil water potential were determined, for each soil and depth in different times. The cohesive layer makes difficult the water flow in the soil profile, both in the wetting and in the drying processes. Consequently, the total water potential in soils with cohesive layer changed abruptly in the most superficial layer, during the time, and slowing in the deepest layers. In non-cohesive soil, the water potential changed abruptly only in the most superficial layer. The -1,500 kPa limit of soil water pressure as permanent wilting point is not applied to orange crop.